Copy number analysis of 413 isolated talipes equinovarus patients suggests role for transcriptional regulators of early limb development - Alvarado, David M (Nature Publishing Group, 2013)
Talipes equinovarus is one of the most common congenital musculoskeletal anomalies and has a worldwide incidence of 1 in 1000 births. A genetic predisposition to talipes equinovarus is evidenced by the high concordance rate in twin studies and the increased risk to first-degree relatives. Despite the frequency of isolated talipes equinovarus and the strong evidence of a genetic basis for the disorder, few causative genes have been identified. To identify rare and/or recurrent copy number variants, we performed a genome-wide screen for deletions and duplications in 413 isolated talipes equinovarus patients using the Affymetrix 6.0 array. Segregation analysis within families and gene expression in mouse E12.5 limb buds were used to determine the significance of copy number variants. We identified 74 rare, gene-containing copy number variants that were present in talipes equinovarus probands and not present in 759 controls or in the Database of Genomic Variants. The overall frequency of copy number variants was similar between talipes equinovarus patients compared with controls. Twelve rare copy number variants segregate with talipes equinovarus in multiplex pedigrees, and contain the developmentally expressed transcription factors and transcriptional regulators PITX1, TBX4, HOXC13, UTX, CHD (chromodomain protein)1, and RIPPLY2. Although our results do not support a major role for recurrent copy number variations in the etiology of isolated talipes equinovarus, they do suggest a role for genes involved in early embryonic patterning in some families that can now be tested with large-scale sequencing methods.